ANALISIS HUKUM TINDAKAN MENYEBARKAN BERITA BOHONG YANG MENGAKIBATKAN KEONARAN MELALUI MEDIA ELEKTRONIK (ANALISIS PUTUSAN NOMOR:296/PID-SUS/2020/PN-SRH) - Panjaitan, Dian Affandi; Eddy, Triono (JURNAL DOKTRIN REVIEW, 2023)
The criminal case of spreading false news through electronic media using the Facebook application, in the jurisdiction of the Sei Rampa District Court, the case has been examined in case Number: 296/Pid-Sus/2020/PN-Srh, but the application of the law given is deemed inappropriate with the facts of the trial. The formulation of the problem is what the perspective of criminal law is regarding the act of spreading fake news which causes chaos through electronic media, and how criminal law is applied to perpetrators of spreading fake news, as well as how the judge considers perpetrators of spreading fake news. The research method used is normative legal research. The results of the discussion found that the act of spreading fake news which caused chaos through electronic media was regulated in Article 28 paragraphs (1) and (2) of the ITE Law, and the application of criminal law to perpetrators of spreading fake news in the decision by the Public Prosecutor using Article 14 paragraph 1 Law No. 1 of 1946 concerning Criminal Law Regulations, in conjunction with Article 27 paragraph 3 of the ITE Law, but in his Demand Letter the Prosecutor applied Article 27 paragraph 3 of the ITE Law against the Defendant, but the Prosecutor did not apply Article 28 paragraph (2) of the ITE Law. as well as the judge's consideration of the perpetrator of spreading fake news which caused chaos through electronic media in Decision Number: 296/Pid-Sus/2020/PN-Srh, which stated that the defendant was guilty of violating Article 27 paragraph 3, even though the defendant's actions tended to violate Article 14 paragraph 1 Law No. 1 of 1946 concerning Criminal Law Regulations. The criminal act of spreading fake news should be more comprehensively regulated in the ITE Law, so that there is no need to apply Law Number: 1 of 1946.